Comparative Analysis of Strengthening Factors Intergenerational Purchasing Decisions in Jabodetabek - Agus Kusnawan; Diana Silaswara; Eso Hernawan (LPPM Universitas Buddhi Dharma, 2025)
Every person's purchasing decisions will always be different according to their individual characteristics. Consumer behaviour and purchasing behaviour of each generation are very different. Based on this, this research was carried out to determine the differences in factors that strengthen purchasing decisions in each generation studied, namely generations X, Y, and Z, which are the most numerous and productive currently. This research is quantitative in nature, and the research analysis method uses causal descriptive and SPSS (multiple regression) analysis tools. Initially, the number of respondents needed was calculated, after knowing that the population of Jabodetabek was around 30.2 million people. Using Slovin calculations with a value of E = 10%, with minimum sample of 100 respondents was obtained. Based on data from 308 valid questionnaires obtained from the Jabodetabek population (30.2 million people), it is known that service quality most important thing is for generations X and Y, the difference lies in the order after that which is for generations and discounts, meanwhile for generation Y there is a sequence of lifestyle, product quality, n and discounts (by (Ramdhani, n.d.) which states that generation Y works to support their lifestyle). In contrast to the previous two generations, Gen Z prioritizes service quality after product quality.